An Innovative Approach to Improve Canada’s Infectious Disease Pandemic Rapid Response in Marginalized Communities - Raithby, Georgia Leigh; De Leon, Josephine; Karra-Aly, Ayah; Osman, Amina Abib; Boyd, Cara Lynne; Saini, Gurleen Kaur; Sehra, Jasandeep Singh; Ikenyei, Uche Chukwuka (Global Health: Annual Review, 2020)
.